AN ANALYSIS OF TEACHER QUESTIONING IN THE CLASSROOM INTERACTION - apriani, reni; marchelina, diana (PROJECT (Professional Journal of English Education), 2018)
Teaching learning process will be effective when there are interactions between the teacher and students. Classroom interaction is one of the crucial factors in the teaching-learning process. Questioning has been recognized as the equipment of classroom teachers and profound to prominent teaching. The objective of this research is to identify the types of basic questions the teacher asks. The research method used descriptive qualitative design. The data were obtained by doing observation and interview with the educator and students as respondent. The population of this research was teacher and students of the second-grade students of SMK TI Garuda Nusantara Cimahi. The data were investigated by applying questioning strategies focused on the variety of teacher questioning. The result showed that entire teacher questioning that found the most frequently used. Based on the result, it can be concluded that the questioning from the teacher was more dominant than student questions.